When You "Can't See" a Case of Relapsing Polychondritis - David Contreras MD; Navpreet Dhillon BS; Rupam Sharma MD; Varun Bali MD; Sabetian Katayon MD; Bao Quynh Huynh MD; Arash Heidari MD (SAGE Publishing, 2021)
Relapsing polychondritis (RP) is a rare and, if not treated, potentially lethal autoimmune disorder. Involvement of central nervous system (CNS) in RP is rare and, when present, makes it extremely difficult to diagnose. In this report, we present a case of a 22-year-old Hispanic woman who presented with sudden onset of headache and blurred vision. Magnetic resonance imaging (MRI) of her brain and orbit showed leptomeningeal enhancements in addition to asymmetrical thickening and enhancement of globes. Her lumbar puncture was consistent with aseptic meningitis picture, and she was placed on empirical treatment for presumptive CNS tuberculosis. Her vision deteriorated, and she was diagnosed with RP with CNS and ocular involvement and placed on high-dose steroids with dramatic rapid response. She has been on immunosuppressive treatment, including Sulfasalazine and Methotrexate, since then and her disease has been under control with decreased need for ophthalmic steroid drops. There have been only 19 previous cases found in literature reporting an association of RP with CNS involvement.